Analisis Peran DLH Bukittinggi dalam Pengelolaan Sampah - Iqbal Faizul Candra; Daniel Arif Hendrawan; Syamsir Syamsir (Lembaga Yasin AlSys, 2026)
Waste management is one of the most pressing environmental issues in developing cities, including Bukittinggi City, and therefore requires governance that is effective, sustainable, and compliant with regulatory frameworks. The Dinas Lingkungan Hidup (DLH) of Bukittinggi, as the competent authority, plays a strategic role in directing and coordinating various solid waste programs. This study aims to analyze the role of DLH Bukittinggi in waste management, encompassing its functions in planning, implementation, supervision, environmental education, and cooperation with communities and third parties. The research employed a descriptive qualitative approach through literature review, document analysis, and policy analysis related to local waste governance. The results indicate that DLH Bukittinggi has implemented several waste management programs, including the development of waste banks (bank sampah), the provision of waste management facilities and infrastructure, waste reduction at the source, and transportation and final processing at the Tempat Pemrosesan Akhir (TPA) facility. Nevertheless, the implementation of these programs still faces multiple challenges, such as limited waste collection fleets, low community participation in waste sorting, and the need to strengthen education and supervision. The study concludes that optimizing the role of DLH Bukittinggi requires strengthening institutional capacity, fostering multisectoral collaboration, and enhancing public awareness so that the waste management system can operate more efficiently and sustainably. These findings are expected to serve as a basis for evaluation and recommendations to improve waste management policies in Bukittinggi City.